Hubungan Sensory Profile Dengan Kemandirian Aktifitas Fungsional Dan Prestasi Akademik Anak Sekolah Dasar (SD) Kelas Satu Di Desa Sawahan, Ngemplak, Boyolali - Lis Sarwi Hastuti; Rina Kurnia (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Sensory Profile, Independence Of Functional Activity, Academic Achievement. This study aims to determine whether there is a relationship between the level of sensory profile with the independence of functional activity and academic achievement of Primary School-aged children in Sawahan Village, Ngemplak, Boyolali. This study uses an analytical study design with cross-sectional correlation. Sampling collection was done by quota sampling technique against first grade in four primary schools in Sawahan village, Ngemplak, Boyolali.The result of Pearson product moment correlation was obtained p-value = 0.000 and (r) = 0.880 for the variable sensory profile - independence , while variable sensory profile - academic achievement obtained p-value = 0.029 and (r) = 0.345. Conclusions results of this research is there a relationship between the sensory profile of the independence and academic achievement of first grade Primary School-aged children in the Sawahan village, Ngemplak District, Boyolali. It shows the higher score obtained by children in SSP (child closer to typical performance or is at a normal level) either higher the score of independence of the child (the child more independent) and academic achievement is getting better and otherwise.